HUBUNGAN KONDISI SANITASI DASAR DENGAN KELUHAN KESEHATAN DIARE SERTA KUALITAS AIR PADA PENGGUNA AIR SUNGAI DELI DI KELURAHAN SUKARAJA KECAMATAN MEDAN MAIMUN TAHUN 2012 - Yuki Laura Angeline; Irnawati Marsaulina; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
Correlation between basic sanitary condition and Diarrhea with the water quality in Sukaraja Subdistrict Medan Maimun District 2012. Diarrhea on Deli river users was fairly high. The cause was suspected by unhealthy basic sanitation and people’s habits in using river water as water source. The study aimed to analyze the correlation between condition of basic sanitation and diarrheaon Deli river users and to know Deli water riverquality. The study was conducted by descriptive method with cross sectional study design. This research conducted along the riverside area of Deli on Sukaraja village Medan Maimun Sub District with 59 housewives sample.The result showed there was correlation between sanitation of water resources (p=0,024), family latrines (p=0,016), garbage disposal (p=0,045) and diarrhea, and there was no correlation between sanitation of waste water treatment (p=0,050) and diarrhea. From the results oflaboratory tests,river water quality in upstream area did not exceed the the specified threshold value, such as temperature, nitrate, selenium, and E. coli. According to PP no. 82 tahun 2001, while in middle and downstream area number of E. Coli was foundhad exceeded the specified threshold value. Based on the result of study, Deli river in middle and downstream area had contaminated by feces and there was a significant correlation betweenbasic sanitation and diarrhea. Suggested forLocal Government Medan District to be more intensive on water supply and environmental health program and people to care about their basic sanitation. Keywords : Diarrhea, basic sanitation, river water quality